The morphostructures of the mountainous part basin river Bystrica Nadvirnianska in Ukrainian Carpathians - Brusak, Vitaliy F.; Klapchuk, Taras V. (Journal of the Belarusian State University. Geography and Geology, 2017)
In the article author characterized the morphostructures of the mountainous part basin river Bystrica Nadvirnianska which are located in the north-eastern slopes of the Ukrainian Carpathians. For the first time, it was presented a large-scale map of the morphostructures of the river basin which was created by the means of GIS, also it was made data base of a tectonic and geological structure, morphological and morphometric characteristics of the relief. The studies confirmed the validity of existing medium-scale schemes of morphostructures in the region and significantly refined the boundaries of morphostructures of different orders, using the means of GIS. In the territory of research identified 2 morphostructures of the first order: Skybovi and Vododilno-Verkhovynski Carpathians, which are confined to areas of major tectonic zones – Skybova cover and area of Krosno. In their boundaries allocated 7 morphostructures of the second order, confined to smaller tectonic units. In Skybova Carpathians there are the individual skyb, Beregova, Orivska, Skolivska, Parashka and Zelemyanka. In Vododilno-Verkhovynski Carpathians morphostructures of the second order which correspond of two tectonic subdivisions: Yasinya-Putyla lowland and Serednovystne horstopodibne raising Pryvododilni (Internal) Gorgan. Within the morphostructures of the second order, 11 morphostructures of the third and 8 morphostructures of the fourth order are identified, their geological structure, morphology and morphometry are characterized.
Keywords: Ukrainian Carpathians; Vododilno-Verkhovynski Carpathians; Skybovi Gorgany; morphostructures; relief; tectonic zone; basin river Bystrica Nadvirnianska; GIS